STRATEGIES FOR IMPROVING PUBLIC SERVICES THROUGH THE SIMAS BISMA WEBSITE AT THE CLASS I MALANG CORRECTIONAL CENTER - Prabowo, Hadi; Iskandar, Irvan Sebastian (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Client expectations for quick and simple service define need for Bapas I Malang to be able to satisfy these needs. The goal of this research is to investigate the strategies and t method employed by Bapas I Malang to improve the quality of public services through the SIMAS BISMA website innovation. This is descriptive qualitative research that is analyzed utilizing the theories of service improvement strategies and innovation success. The findings of this study show that the strategies used were successfully implemented in meeting each indicator of the strategy in the service improvement strategy, implying that in order to provide the best public services for every level of society in the Malang korwil, the service improvement strategy approach used must be optimized and adjusted more to the needs of local clients. Keywords: Public Service; Simas Bisma; Improvement Strategy